The Renewal of National Criminal Law: An Analysis of the Pancasila Law Philosophy - Fajrin, Yaris Adhial; Kurniawan, Kukuh Dwi; Ishwara, Ade Sathya Sanathana (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Reform of criminal law is an important aspect in organizing the politics of criminal law so that it can meet the legal needs of society. The legal philosophy of Pancasila occupies an important position in efforts to reform criminal law.Purposes of the Research: Reflection on criminal law renewal in terms of the legal philosophy of Pancasila.Methods of the Research: Normative legal research with conceptual, statutory and philosophical approaches.Results of the Research: The legal philosophy of Pancasila has relevance in relation to the reform of criminal law, including that the philosophy of Pancasila law can be a guide as well as a guide in both normative aspects and the practice of criminal law reform. In addition, the legal philosophy of Pancasila can also direct the orientation of criminal law reform in order to improve five important aspects of criminal law reform, namely aspects of legal substance, culture, structure, leadership, and the professionalism of law enforcement officials. The reading of Pancasila values in a hierarchical-pyramidal manner is important as a guide and direction for a criminal law reform process. Pancasila's legal philosophy has also become a norm of criticism in criminal law reform, namely providing criticism of norms and legal behavior of criminal law reform whether it is in accordance with Pancasila values or not.